Mini-consolidations or intermediate-dose cytarabine for the post-remission therapy of AML patients over 60: a retrospective study from the DATAML and SAL registries - Recher, Christian; Dumas, Pierre-Yves; Bérard, Emilie; Tavitian, Suzanne; Leguay, Thibaut; Galtier, Jean; Alric, Camille; Bidet, Audrey; Delabesse, Eric; Rieu, Jean Baptiste; Vial, Jean-Philippe; Vergez, François; et al. (American journal of hematology, 2025)
According to current recommendations, older AML patients in first complete remission (CR) after induction chemotherapy should receive consolidation with intermediate-dose cytarabine (IDAC). However, no study has demonstrated the superiority of IDAC over other regimen. In this retrospective study, we compared the efficacy of mini-consolidations (idarubicin 8 mg/m2 day 1, cytarabine 50 mg/m2/12 h, day 1-5) and IDAC. Inclusion criteria were newly diagnosed AML, age > 60 years, first CR after induction and at least 1 cycle of consolidation. Of the 796 included patients, 322 patients received mini-consolidations and 474 patients received IDAC. Mini-consolidation patients were older, and more often, they had de novo AML and unfavorable risk. The rate of allogeneic transplantation was higher in the IDAC group. The median number of cycles was higher in the mini-consolidation group (4 vs. 2; p < .0001). Median relapse-free survival was 18 months with mini-consolidations and 12 months with IDAC (p = .0064). In multivariate analysis, the risk of relapse or death was significantly higher in the IDAC group (p = .004). Median OS was 36 versus 31 months with mini-consolidations or IDAC, respectively (p = .46). In multivariate analysis, the consolidation regimen had no significant influence on OS (p = .43). In older AML patients, post-remission therapy with mini-consolidations represents an alternative to IDAC.